2011
DOI: 10.1111/j.1468-2370.2010.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Online Customer Experience: A Review of the Business-to-Consumer Online Purchase Context

Abstract: Customer interactions with an organization's website create opportunities for positive experiences that can lead to long-term relationship building. The range of potential interactions is now quite diverse, including product information search, purchase transaction and/or service delivery. The domain of customer experience (CE) is well developed in the face-to-face context, but little attention has been paid to exploring the concept in the online context. The purpose of this paper is to provide a review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
273
1
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(295 citation statements)
references
References 109 publications
4
273
1
17
Order By: Relevance
“…In turn, the relationship between e-satisfaction and reliability is supported by the studies of Rose et al (2011), who found that websites that are associated with greater confidence tend to reduce the perception of risk associated with e-commerce and elicit favorable attitudes from consumers, increasing satisfaction. Therefore, as greater the confidence in the retail brand, lower is the cognitive dissonance or discomfort of the individual after placing the purchase order, which tends to positively influence the online satisfaction (Rose et al, 2011;Fasanghari and Roudsari, 2008;Schaupp and Belanger, 2005).…”
Section: Endogenousmentioning
confidence: 53%
See 1 more Smart Citation
“…In turn, the relationship between e-satisfaction and reliability is supported by the studies of Rose et al (2011), who found that websites that are associated with greater confidence tend to reduce the perception of risk associated with e-commerce and elicit favorable attitudes from consumers, increasing satisfaction. Therefore, as greater the confidence in the retail brand, lower is the cognitive dissonance or discomfort of the individual after placing the purchase order, which tends to positively influence the online satisfaction (Rose et al, 2011;Fasanghari and Roudsari, 2008;Schaupp and Belanger, 2005).…”
Section: Endogenousmentioning
confidence: 53%
“…Lee and Kozar (2006) argue that the brand reputation of a retailer is a factor of attraction, retention, and customer satisfaction. Brands arouse greater consumer confidence, reduce the perception of risk associated with e-commerce, and increase online satisfaction (Rose et al, 2011).…”
Section: Attributes Of Online Shopping Experience That Influence E-samentioning
confidence: 99%
“…Esse fato, aliado aos detalhes apresentados acima, permite concluir que a experiência geral com o website oficial da Islândia foi considerada positiva pelos sujeitos da pesquisa. Esse resultado vai ao encontro do que é destacado na literatura por Rose et al (2011), que propõe um modelo onde os gestores precisam estar cientes de que, desempenho funcional de um site é importante, mas também é essencial compreender o estado vivencial e as respostas dos clientes susceptíveis de serem geradas pelo website. E essa resposta se dá somente a partir da experiência online.…”
Section: Conteúdo Das Informaçõesunclassified
“…Terms can either be retrieved directly from the interfacing Website (e.g. though an existing taxonomy or folksonomy) or through term extraction tools such as Yahoo JQL table 1 . In a second stage the extracted terms can be used to receive related terms through external knowledge services such as WordNet 2 or openCalais 3 .…”
Section: The Unite Architecturementioning
confidence: 99%
“…It can be argued that the main reason for this shortcoming is the need for Website owners to encourage users to remain within their Website as long as possible. The expected outcome of a prolonged user visit is an increase in revenue either during the visit or in future visits [1]. The user on the other hand benefits from Website specific personalisation by receiving personalised recommendations, such as purchase related items, that may be of interest to the user.…”
Section: Introductionmentioning
confidence: 99%